Design, Synthesis, Antibacterial Evaluation, Three-Dimensional Quantitative Structure–Activity Relationship, and Mechanism of Novel Quinazolinone Derivatives - Shao, Lihui; Zhao, Su; Yang, Song; Zhou, Xiang; Li, Yan; Li, Chengpeng; Chen, Danping; Li, Zhuirui; Ouyang, Guiping; Wang, Zhenchao (Journal of agricultural and food chemistry, 2023)
Plant bacterial illnesses are common and cause dramatic damage to agricultural goods all over the world, yet there are few efficient bactericides to alleviate them at present. To discover novel antibacterial agents, two series of quinazolinone derivatives with novel structures were synthesized and their bioactivity against plant bacteria was tested. Combining CoMFA model search and the antibacterial bioactivity assay, D32 was identified as a potent antibacterial inhibitor against Xanthomonas oryzae pv. Oryzae (Xoo), with an EC50 value of 1.5 μg/mL, much better in inhibitory capacity compared to bismerthiazol (BT) and thiodiazole copper (TC) (31.9 and 74.2 μg/mL). The activities of compound D32 against rice bacterial leaf blight in vivo were 46.7% (protective activities) and 43.9% (curative activities), better than commercial drug thiodiazole copper (29.3% protective activities and 30.6% curative activities). Flow cytometry, proteomics, reactive oxygen species, and key defense enzymes were used to further investigate the relevant mechanisms of action of D32. The identification of D32 as an antibacterial inhibitor and revelation of its recognition mechanism not only open the possibility of developing new therapeutic strategies for treatment of Xoo but also provide clues for elucidation of the acting mechanism of quinazolinone derivative D32, which is a possible clinical candidate worth in-depth study.